The cytoprotective drug rebamipide in therapy for inflammatory and erosive-ulcerative lesions of the gastrointestinal tract - E P Yakovenko; N A Agafonova; A N Ivanov; A V Yakovenko; M A Aldiyarova; T V Volosheinikova; Yu V Grigoryeva; I P Soluyanova (Терапевтический архив, 2016)
Rebamipide is a cytoprotесtive drug that stimulates the generation of endogenous prostaglandins in the gastric and small intestinal mucosa and accelerates the healing of erosions and ulcers caused by Helicobacter pylori infection and NSAID administration. The major properties of rebamipide include stimulation of prostaglandins and synthesis of muсus glycoproteins, inhibition of reactive oxygen species, inflammatory cytokines, and chemokines, and suppression of neutrophil activation. This paper shows the ability of rebamipide to enhance the efficiency of therapy for Helicobacter pylori-induced infection, to reduce inflammation, including that after infection eradication, to accelerate ulcer healing, and to prevent the progression of preneoplastic lesions.